Qui finis erit discordiarum?(1): Two rhetorical speeches in Livy - Jancsovics, Fanni (Sapiens ubique civis, 2023)
(1) Liv. 3, 67, 10. The usage of inserted rhetorical speeches is a crucial point of ancient historiography. After an introduction to the basic arguments of the evaluation of ancient historiography and its connection with theatricality, supplemented by the ‘accusation’ of tragic history I move over to the examination of two speeches found in Livy’s narrative. In order to understand the style of Livy more and more precisely his practice of editing and inserting speeches into the narrative this paper will give a closer look at the initial moment of this particular part of his editorial work. The two speeches in question are from Quinctius Capitolinus and Gaius Canuleius.